Analysis of Students' Problem-Solving Skills in Physics Learning Through a STEM-Oriented Direct Teaching Model - Waasik Murniati; Suyidno Suyidno; Sarah Miriam; Dewi Dewantara; Mazlena Binti Murshed (Jurnal Ilmiah Pendidikan Fisika, 2024)
Problem-solving skills are one of the 21st-century skills that students must master, but most students still have not mastered them. This research aims to describe the implementation and obstacles to implementing STEM-oriented direct instruction to improve students' problem-solving skills. This research is descriptive and qualitative in analyzing students' problem-solving skills. The subjects of this research were 20 students in class XI MIPA. The tools used are sound wave teaching materials that have been validated, and research instruments are student response questionnaires, and researchers act directly as teachers. Data analysis is carried out by reviewing the results obtained in the field through interviews, observations, and a collection of other documents. The data analysis stages in this research used the Miles and Huberman model: data classification, data display, and data validation. It was concluded that the implementation of learning took place according to the STEM-oriented direct instruction syntax, and several factors hindered the improvement of students' problem-solving skills, including internal factors, namely from within the students, and external factors, namely from the teacher and school.